mTOR-Mediated Regulation of Immune Responses in Cancer and Tumor Microenvironment - Mafi, Sahar; Mansoori, Behzad; Taeb, Shahram; Sadeghi, Hossein; Abbasi, Reza; Cho, William C.; Rostamzadeh, Davoud (Frontiers in Immunology, 2022)
The mechanistic target of rapamycin (mTOR) signaling pathway is well recognized to regulate many essential cellular processes including cell growth, survival, proliferation and metabolism by integrating a variety of intracellular and extracellular signals in the tumor microenvironment (TME). The dysregulation of the mTOR pathway has been frequently reported in many types of human tumors and represents an attractive target for therapies. In fact, mTOR plays a pivotal regulatory role in the tumor immune microenvironment. As the core regulator of metabolic and translational reprogramming, mTOR can affect tumor-associated immune cells to undergo phenotypic and functional reprogramming in TME. The mTOR-mediated inflammatory response also can promote recruitment of immune cells to TME, resulting in exert the anti-tumor functions or promote tumor cells growth, progression, and metastasis. Thus, deregulated mTOR signaling in cancer can modulate the TME, thereby affecting and shaping tumor immune microenvironment. This review focuses on the current knowledge regarding the key role of the mTOR signaling pathway in controlling and shaping the immune responses in TME.